The diagnosis and medical management of advanced neuroendocrine tumors. - Kaltsas, G; Besser, G; Grossman, A (2004)
Neuroendocrine tumors (NETs) constitute a heterogeneous group of neoplasms that originate from endocrine glands such as the pituitary, the parathyroids, and the (neuroendocrine) adrenal, as well as endocrine islets within glandular tissue (thyroid or pancreatic) and cells dispersed between exocrine cells, such as endocrine cells of the digestive (gastroenteropancreatic) and respiratory tracts. Conventionally, NETs may present with a wide variety of functional or nonfunctional endocrine syndromes and may be familial and have other associated tumors. Assessment of specific or general tumor markers offers high sensitivity in establishing the diagnosis and can also have prognostic significance. Imaging modalities include endoscopic ultrasonography, computed tomography and magnetic resonance imaging, and particularly, scintigraphy with somatostatin analogs and metaiodobenzylguanidine. Successful treatment of disseminated NETs requires a multimodal approach; radical tumor surgery may be curative but is rarely possible. Well-differentiated and slow-growing gastroenteropancreatic tumors should be treated with somatostatin analogs or alpha-interferon, with chemotherapy being reserved for poorly differentiated and progressive tumors. Therapy with radionuclides may be used for tumors exhibiting uptake to a diagnostic scan, either after surgery to eradicate microscopic residual disease or later if conventional treatment or biotherapy fails. Maintenance of the quality of life should be a priority, particularly because patients with disseminated disease may experience prolonged survival.